Sistemas de armazenamento em parques eólicos considerando PLD horário e situações de constrained off - Lima, Mayara Miqueletti de (2021)
Wind generation in Brazil has been growing since 2009, the year of the first energy auctions, and in 2020, it is considered a consolidated source of renewable energy. The consolidation of the wind source has brought an increase in competitiveness in the sector and, consequently, a significant drop in energy auctions’ prices. In the scope of trade energy, contracting models in Brazil have followed the sector’s development, where contracting in the free energy market mode has stood out in comparison to contracts in the regulated market. In addition to changes in the energy contracting model in the wind sector, Brazil’s energy pricing form is also undergoing substantial changes. The spot price, calculated weekly and developed for a predominantly hydraulic matrix, was replaced in 2021 by an hourly spot price seeking more outstanding financial balance in the market given the electrical system’s operation. For wind energy producers, the implementation of an hourly price entails more significant financial risks, especially for wind projects contracted in the free energy market, since hourly PLD has more significant intraday variability than the weekly price. In addition to the risks linked to the implementation of hourly prices, wind farms may also suffer reductions in financial revenue caused by generation limitation events (Constrained Offs). Because of the increase in economic risks linked to the implementation of the hourly price in 2021, and the situations of Constrained Offs in wind farms in Brazil, this research proposes a methodology for assessing the applicability of lithium-ion storage energy systems in wind farms in the free market. Within the scope of hourly price, the methodology developed proposes using storage systems to lessen wind farm revenues in the face of intraday variations in the hourly price and Constrained Offs, choosing to store it at low cost and dispatch it at more good times. The proposed methodology did apply to three real wind complexes located in Rio Grande do Norte, Bahia and Rio Grande do Sul states. The results demonstrate that storage systems can bring considerable benefits to wind farm revenues; however, the high cost of implementing storage systems considering only this application proved unfeasible.